21 PTT and Anti-Xa Activity in Adult Mechanical Circulatory Support Patients at a Large Academic Medical Center. (11th January 2018) - Saifee, Nabiha; Mahr, Claudius; Garcia, David; Estergreen, Joanne; Sabath, Daniel
Abstract: In mechanical circulatory support (MCS) patients, proper heparin dosing is critical to avoid circuit thrombosis and bleeding complications; however, PTT and anti-Xa activity tests used for heparin monitoring may be discordant. In order to better characterize this discordance, we describe data from adult MCS patients for six months of paired PTT/anti-Xa activity and eight months of PTT/anti-Xa activity with concurrent laboratory results for PT, antithrombin antigen (ATAg), factor VIII (F8), and C-reactive protein (CRP). At our institution, the therapeutic range for unfractionated heparin is 0.30–0.70 IU/mL for anti-Xa activity and 60–100 seconds for PTT. Concordance between PTT and anti-Xa activity is defined as PTT<60 seconds and anti-Xa <0.3 IU/mL, PTT 60–100 seconds and anti-Xa activity 0.3–0.7 IU/mL, or PTT>100 seconds and anti-Xa activity >0.7 IU/mL. A retrospective review of adult MCS patients from May 1, 2016 to October 19, 2016 representing 2, 078 paired PTT/anti-Xa measurements from 96 patients revealed only 593 (28.5%) were concordant. Of the remaining 1485 discordant pairs, 16 had anti-Xa activity results greater than expected for the paired PTT, and 1, 469 (98.9%) had PTT results greater than expected for the paired anti-Xa activity. From June 1, 2016 to January 31, 2017, clinicians concerned about discordant PTT/anti-Xa activity ordered a battery of tests, including a 1:1 mixing study of PT, PTT, thrombin time (TT) with heparinase treatment, ATAg, F8 activity, and CRP. For 104 samples from 71 patients, only 12 demonstrated concordance, while 92 showed discordance—all with higher than expected PTT values. The panel was preferentially ordered for supratherapeutic PTT >100 seconds (69/92), and none of the discordant samples had anti-Xa activity>0.7 IU/mL. The remaining 23 discordant samples had therapeutic PTT 60–100 seconds with 16 samples having subtherapeutic anti-Xa activity 0.1–0.3 IU/mL and seven having no evidence of heparin therapy (anti-Xa activity= 0 and normal TT). The majority of discordant samples (72/92) had an elevated PT indicating coagulation factor deficiency. For the 85 discordant samples with evidence of heparin therapy, ATAg ranged from 31% to 120% with only two below 50%. After heparinase treatment of 85 samples, 76 still had a PTT result above the reference range, suggesting PTT assay interference in 89% of discordant samples with heparin. CRP has been shown to cause PTT assay interference in vitro, while elevated F8 may shorten PTT. In the discordant group, CRP ranged from 2.9 to 471.6 mg/L and F8 activity ranged from 123% to >400%, but neither showed a correlation with PTT. In conclusion, a majority of adult MCS patients will have a PTT prolonged compared to anti-Xa activity. The major cause for this discordance appears to be coagulation factor deficiency and/or PTT assay interference rather than low ATAg, elevated CRP, or elevated F8. For MCS patients, anti-Xa activity should be used to monitor heparin therapy in concert with PT to assess for concurrent factor deficiency.